ROLE OF RUKSHAN CHIKITSA IN THE MANAGEMENT OF AAMVATA - A CASE STUDY: Array - Bhujade, Anagha Hanwantrao; Magare, Mukund Dinkarrao (Ayurline: International Journal of Research in Indian Medicine, 2019)
ABSTRACT ROLE OF RUKSHAN CHIKITSA IN THE MANAGEMENT OF AAMVATA - A CASE STUDY. Rheumatoid Arthritis is a chronic inflammatory disease of joint characterised by symmetrical peripheral poly arthritis. The clinical incidence of RA increases between 25 to 55 years of age, after which it plateaus until the age of 75 and then decreases. RA affects approximately 0.5-1 % of the adult population worldwide. RA affects the synovial tissue underline cartilage and bone. Genetic, environmental and immunological factors play role in pathogenesis of the disease. It is comparable to the disease Aamvata in Ayurveda. The symptoms of Aamvata are produced due to vitiation of Vata along with formation of Aama. The Aama gets deposited into the Shleshmasthana and the joints with Sthanavaigunya. It produces features like joint pain (Sandhishool) and joint swelling (Sandhishotha). Aamvata is first explained by Aacharya Madhavkara and treatment is explained in Yogratnakara. The treatment modalities like Langhan (fasting therapy), Rukshan , swedan(fomentation therapy), Deepan , Virechan, Basti are advised in samhitas. In present study a male patient having features of Aamvata treated with Langhan (Rukshan), Swedan for Shaman purpose. Rukshan therapy given for 7 days in IPD level. The assessment was done on the basis of reduction in swelling, improvement in range of movement and improvement in walking. Patient showed remarkable changes after treatment. KEYWORDS Aamvata, Shleshmasthan, Sthanvaigunya, Rukshan